Metagenomic Sequencing and Reverse Transcriptase PCR Reveal That Mobile Phones and Environmental Surfaces Are Reservoirs of Multidrug-Resistant Superbugs and SARS-CoV-2 - Boucherabine, Syrine; Nassar, Rania; Zaher, Shroque; Mohamed, Lobna; Olsen, Matthew; Alqutami, Fatma; Hachim, Mahmood; Alkhaja, Abdulmajeed; Campos, Mariana; Jones, Peter; McKirdy, Simon; Alghafri, Rashed; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Mobile phones of healthcare workers (HCWs) can act as fomites in the dissemination of microbes. This study was carried out to investigate microbial contamination of mobile phones of HCWs and environmental samples from the hospital unit using a combination of phenotypic and molecular methods. Methods This point prevalence survey was carried out at the Emergency unit of a tertiary care facility. The emergency unit has two zones, a general zone for non-COVID-19 patients and a dedicated COVID-19 zone for confirmed or suspected COVID-19 patients. Swabs were obtained from the mobile phones of HCWs in both zones for bacterial culture and shotgun metagenomic analysis. Metagenomic sequencing of pooled environmental swabs was conducted. RT-PCR for SARS-CoV-2 detection was carried out. Results Bacteria contamination on culture was detected from 33 (94.2%) mobile phones with a preponderance of Staphylococcus epidermidis (n/N = 18/35), Staphylococcus hominis (n/N = 13/35), and Staphylococcus haemolyticus (n/N = 7/35). Two methicillin-sensitive and three methicillin-resistant Staphylococcus aureus, and one pan-drug-resistant carbapenemase producer Acinetobacter baumannii were detected. Shotgun metagenomic analysis showed high signature of Pseudomonas aeruginosa in mobile phone and environmental samples with preponderance of P. aeruginosa bacteriophages. Malassezia and Aspergillus spp. were the predominant fungi detected. Fourteen mobile phones and one environmental sample harbored protists. P. aeruginosa antimicrobial resistance genes mostly encoding for efflux pump systems were detected. The P. aeruginosa virulent factor genes detected were related to motility, adherence, aggregation, and biofilms. One mobile phone from the COVID-19 zone (n/N = 1/5; 20%) had positive SARS-CoV-2 detection while all other phone and environmental samples were negative. Conclusion The findings demonstrate that mobile phones of HCWs are fomites for potentially pathogenic and highly drug-resistant microbes. The presence of these microbes on the mobile phones and hospital environmental surfaces is a concern as it poses a risk of pathogen transfer to patients and dissemination into the community.